Sistem Informasi Pengaduan Masyarakat Desa Berlian Jaya Berbasis Mobile Menggunakan Metode Extreme Programming - Monica Silvy; Andri; Fatoni; Edi Supratman (PPPM Institut Teknologi Pagar Alam, 2025)
The community complaint process in Berlian Jaya Village is still carried out directly with a special application used, where residents must submit complaints to village officials through face-to-face meetings or telephones, in addition, verification, and receipt of complaints are also managed directly without an integrated digital system. This condition causes the complaint process to be less efficient, unstructured, and difficult to monitor by the public. This research aims to design and implement a Mobile-Based Berlian Jaya Village Community Complaint Information System to improve service effectiveness, transparency, and accuracy of complaint documentation. The system development method uses Extreme Programming (XP) which consists of planning, design, coding, and testing stages. The system modeling is carried out using the Unified Modeling Language (UML) which includes use case diagrams, activity diagrams, and class diagrams. The system test is carried out using the black box testing method to ensure that all functions run according to the scenario. The results of the study show that the system built is able to facilitate the community in submitting complaints online, accelerate the response of village officials, provide real-time complaint history and status, and produce structured and accurate reports, thereby increasing the efficiency and transparency of complaint management in Berlian Jaya Village.